Chemical and biological evaluation of amazonian medicinal plant vouacapoua americana aubl - Çiçek, Serhat Sezai (2022)
Vouacapoua americana (Fabaceae) is an economically important tree in the Amazon region and used for its highly resistant heartwood as well as for medicinal purposes. Despite its frequent use, phytochemical investigations have been limited and rather focused on ecological properties than on its pharmacological potential. In this study, we investigated the phytochemistry and bioactivity of V. americana stem bark extract and its constituents to identify eventual lead structures for further drug development. Applying hydrodistillation and subsequent GC-MS analysis, we investigated the composition of the essential oil and identified the 15 most abundant components. Moreover, the diterpenoids deacetylchagresnone (1), cassa-13(14),15-dien-oic acid (2), isoneocaesalpin H (3), (+)-vouacapenic acid (4), and (+)-methyl vouacapenate (5) were isolated from the stem bark, with compounds 2 and 4 showing pronounced effects on Methicillin-resistant Staphylococcus aureus and Enterococcus faecium, respectively. During the structure elucidation of deacetylchagresnone (1), which was isolated from a natural source for the first time, we detected inconsistencies regarding the configuration of the cyclopropane ring. Thus, the structure was revised for both deacetylchagresnone (1) and the previously isolated chagresnone. Following our works on Copaifera reticulata and Vatairea guianensis, the results of this study further contribute to the knowledge of Amazonian medicinal plants.